2010
DOI: 10.1213/ane.0b013e3181cfc416
|View full text |Cite
|
Sign up to set email alerts
|

Low Tidal Volume and High Positive End-Expiratory Pressure Mechanical Ventilation Results in Increased Inflammation and Ventilator-Associated Lung Injury in Normal Lungs

Abstract: Comparing intraoperative strategies, ventilation with high PEEP resulted in increased production of inflammatory markers. Low PEEP resulted in lower levels of inflammatory markers. High Vt/low PEEP resulted in less histologic lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
5
45
0
Order By: Relevance
“…This is in agreement with previous studies where VT close to 15 mL/kg were maintained with PIP between 22 (Moens et al 1998) and 30 cmH 2 O (Hubbell et al 2011). In humans under general anesthesia, VT as low as 6 mL/kg did not induce more lung atelectasis than traditional VT (Cai et al 2007), but high pressures and large volumes induced more lung injury (Hong et al 2010). Still, the influence of PIP and VT on development of atelectasis in healthy lungs of horses during general anesthesia is not well characterized.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with previous studies where VT close to 15 mL/kg were maintained with PIP between 22 (Moens et al 1998) and 30 cmH 2 O (Hubbell et al 2011). In humans under general anesthesia, VT as low as 6 mL/kg did not induce more lung atelectasis than traditional VT (Cai et al 2007), but high pressures and large volumes induced more lung injury (Hong et al 2010). Still, the influence of PIP and VT on development of atelectasis in healthy lungs of horses during general anesthesia is not well characterized.…”
Section: Discussionsupporting
confidence: 92%
“…The general principle that shortening exhalation times can prevent end-expiratory collapse without an increase in intrinsic PEEP, however, was also demonstrated in the study by Syringe et al (34), in that study by increasing RR. Other potential mechanisms of VILI that could accompany IRV, such as higher static stretch and higher mean airway pressures, possibly resulting in increased inflammation (35)(36)(37)(38), were not addressed in our study. IRV also carries some risk of increasing intrinsic PEEP, if not carefully monitored.…”
Section: Discussionmentioning
confidence: 95%
“…16,17 Indeed, recently an experimental study suggested that such strategy might even lead to increased inflammation and lung injury in normal lungs. 18 Despite these pathophysiological considerations, the use of PEEP in the operating room is controversial. Recently, an observational study conducted in 28 centers in France revealed that most patients undergoing general surgery were ventilated without PEEP.…”
Section: Severgnini Et Almentioning
confidence: 99%